Implementasi Shariah Governance serta Implikasinya terhadap Reputasi dan Kepercayaan Bank Syariah - Rahman El Junusi (IAIN Ponorogo, 2012)
Syariah banking is currently growing rapidly and become part of financial life in the Islamic world. However, there are two important realities to observe in the life of Islamic Banking in Indonesia. First, Islamic banks are faced with a market share that has not met the target by 5 percent. Second, compliance of Islamic banking to Islamic principles was decline. Therefore, it is needed a strategy of development through the implementation of syariah governance. Syariah Governance implementation is expected to have an impact on reputation and customer confidence which in turn can increase the market share of syariah banks. Based on this background, the research problem is how the implementation of syariah governance and its impact on the reputation and confidence in Islamic banks. This research object is Muamalat banks operating in Central Java (Semarang, Solo, Purwokerto). The research sample is 200 respondents using the techniques of analytical judgment. Measurement instrument using 1-5 Likert scale, from strongly disagree (STS) untill Strongly Agree (SS). Firth to know implementation of Shariah governance, it is used a quantitative descriptive analysis using the average (mean). Second, to examine the effect of the implementation of Shariah governance to reputation and customer confidence in Islamic banks, it uses Structur Equation Model (SEM) with program AMOS 4.0 Engineering Structural Equation Modeling (SEM) which consists of two kinds of technical analysis, the goodness of fit and regression weight on the SEM to assess the suitability of the model estimation based on measuring the level of significance of some of the goodness of fit good and bad in a model, so the degree of the model accuracy is determined by the cut-off value.This research concluded that calculations of total assessment on the implementation of Shariah Governance Islamic bank (Bank Muamalat) showed an average score of 3.42 7 in good categories. It shows that shariah compliance is a indicator giving biggest contribution in the implementation of Islamic governance. Compliance to sharia is the main factor to costumer in establishing partnership with syariah banks and deciding to retain syariah banks.